Children living with HIV in Europe: do migrants have worse treatment outcomes?. Issue 2 (1st October 2021) - Chappell, Elizabeth; Kohns Vasconcelos, Malte; Goodall, Ruth L.; Galli, Luisa; Goetghebuer, Tessa; Noguera‐Julian, Antoni; Rodrigues, Laura C.; Scherpbier, Henriette; Smit, Colette; Bamford, Alasdair; Crichton, Siobhan; Navarro, Marissa Luisa; et al.
Abstract: Objectives: To assess the effect of migrant status on treatment outcomes among children living with HIV in Europe. Methods: Children aged < 18 years at the start of antiretroviral therapy (ART) in European paediatric HIV observational cohorts where ≥ 5% of children were migrants (defined as born abroad) were included. Three outcomes were considered: (i) severe immunosuppression‐for‐age; (ii) viraemic viral load (≥ 400 copies/mL) at 1 year after ART initiation; and (iii) AIDS/death after ART initiation. The effect of migrant status was assessed using univariable and multivariable logistic and Cox models. Results: Of 2620 children included across 12 European countries, 56% were migrants. At ART initiation, migrant children were older than domestic‐born children (median 6.1 vs. 0.9 years, p < 0.001), with slightly higher proportions being severely immunocompromised (35% vs. 33%) and with active tuberculosis (2% vs. 1%), but a lower proportion with an AIDS diagnosis (14% vs. 19%) (all p < 0.001). At 1 year after beginning ART, a lower proportion of migrant children were viraemic (18% vs. 24%) but there was no difference in multivariable analysis ( p = 0.702), and no difference in severe immunosuppression ( p = 0.409). However, there was a trend towards higher risk of AIDS/death in migrant children (adjusted hazard ratio = 1.51, 95% confidence interval: 0.96–2.38, p = 0.072). Conclusions: After adjusting for characteristics at ART initiation, migrant children have virological and immunological outcomes at 1 year of ART that are comparable to those who are domestic‐born, possibly indicating equity in access to healthcare in Europe. However, there was some evidence of a difference in AIDS‐free survival, which warrants further monitoring.